Strategies on Teaching Introducing to Programming in Higher Education - Sobral, Sónia Rolland (2021)
Teaching and learning how to program are not easy tasks: they can be very challenging. Introductory programming courses traditionally have high rates of failures and dropouts. Teachers and researchers must develop strategies to combat this problem. The purpose of this paper is to analyse the scientific production on strategies on teaching how to program in higher education in journals indexed in an international database’ indexed in Elsevier’s Scopus in the years 2000 to 2019. We provide an up-to-date review of the existing literature. To provide a comprehensive survey, we not only categorize existing strategies but also present detailed descriptions of relevant topics such as Active Learning, Pair Programming, Flipped Classroom and Project Based Learning. The sample was composed by 92 articles in total. The first results obtained by bibliometric analysis showed that publication rates increased slowly but have expanded in the last two years, in which journals the articles are published, which are the organizations and countries that publish the most and which are the most cited articles. The motivation for this study is to bear in mind the research that has been done so that it strategies can be used and experienced by teachers who teach programming to undergraduate students.